Legal regulation of subsoil users responsibility in the People’s Republic of China and the Republic of Kazakhstan - Fang, Li; Amirov Н.К.; Adilgazy С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article deals with issues of legal liability in the field of subsoil use. Also, subsurface users engaged in exploration, extraction, sale and processing of minerals bear social responsibility. The legislation of Kazakhstan and China is aimed at protecting the right of state ownership of the subsoil,ensuring legal liability for violations by subsoil users of environmental requirements, illegal mining,unauthorized mining, mining without licenses and violation of the terms of a contract or license. The legislation of Kazakhstan provides for provisions on the social responsibility of business, including subsoil users. Kazakhstan has norms on the social responsibility of business entities. The laws of the Republic of Kazakhstan establish the obligations of subsoil users for the acquisition of Kazakh goods, works and services, as well as for the training of Kazakhstan staff. The legislation of both countries provides for measures of civil, administrative and criminal responsibility for violations of legislation in the field of subsoil use. Recent events in the world related to the interests of the current US administration in concludingdeals with some countries of the world on the extraction of rare earth metals indicate the geopoliticalnature of the attitude towards the subsoil and subsoil use. The sphere of subsurface use is becoming a sphere of geopolitical interest for major powers. In the case of assuming geopolitical obligations, the State engaged in subsurface use essentially assumes responsibility for the country where subsurface use is carried out.